RETRACTED: The use of digital technologies in physical education classes for students with a weakened state of health - Yekimov Sergey; Firsova Nadezda; Tynnyi Vadym; Mashkova Inna; Ishchenko Tamara; Kuzmenko Diana; Belyakova Olga (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001